2013
DOI: 10.1111/jicd.12033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive ultrasonic irrigation and manual dynamic irrigation on smear layer removal from root canals in a closed apex in vitro model

Abstract: Both activation techniques are important adjuncts in removing the smear layer, with manual dynamic activation being a simpler, safer, and more cost-effective technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
3
18
0
8
Order By: Relevance
“…G2, G5, and G6 showed no significant difference among their scores. Similar to the others studies (Andrabi et al, ; Castagna et al, ) the agitation of the EDTA solution with ultrasound did not increase the efficiency of smear layer removal, but other authors found different results (Arslan et al, ; Capar & Aydinbelge, ; Kuah et al, ). The different results found may be related to the use of human teeth and the modeling of the canal of instruments with smaller diameter.…”
Section: Discussionsupporting
confidence: 82%
“…G2, G5, and G6 showed no significant difference among their scores. Similar to the others studies (Andrabi et al, ; Castagna et al, ) the agitation of the EDTA solution with ultrasound did not increase the efficiency of smear layer removal, but other authors found different results (Arslan et al, ; Capar & Aydinbelge, ; Kuah et al, ). The different results found may be related to the use of human teeth and the modeling of the canal of instruments with smaller diameter.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, it has been reported that the efficacy of PUI can be positively associated with ultrasonic intensity by regulating the amplitude of the file (9). Nonetheless, others have pointed out that PUI might be more complicated, dangerous and expensive than manual dynamic irrigation, based on the results of a study using an in vitro apex model (10). Considering these disagreements regarding the application of PUI, more research on its benefits and disadvantages should be encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…Um dos fatores que podem explicar esta limitação é a dificuldade da solução de alcançar a área apical usando pressão positiva. Porém, atualmente, novos recursos, como a IUP (Irrigação Ultrassônica Passiva), permitem o alcance da solução irrigadora em áreas irregulares, tais como a região de istmo 16 . No presente estudo, realizou-se a IUP ao final da instrumentação em toda a amostra.…”
Section: Discussionunclassified